Introduction: Shakespeare and/in Europe: Connecting Voices - Fayard, Nicole (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
Recent Shakespearean productions, just like current European crises, have highlighted the exclusionary nature of European identity. In defining the scope of this special issue, the aim of this introduction is to shift the study of Shakespeare in/and Europe away from the ideological field of “unity within diversity” and its attendant politics of negotiation and mediation. Instead, it investigates whether re-situating Shakespearean analysis within regimes of exclusionary politics and group conflict attitudes helps to generate dynamic cultural and social understandings. To what effect is Shakespeare’s work invoked in relation with the tensions inherent in European societies? Can such invocations encourage reflections on Europe as a social, political and/or cultural entity? Is it possible to conceptualize Shakespearean drama as offering an effective instrument that connects―or not―the voices of the people of Europe?